STRATEGI DAERAH DALAM PENGELOLAAN SAMPAH RUMAH TANGGA BERDASARKAN PERATURAN BUPATI SUMBAWA NOMOR 46 TAHUN 2019 UNTUK KETAHANAN LINGKUNGAN - Fuji Kusuma Adynata (Nusantara Hasana Journal, 2025)
The issue of household waste in Sumbawa Regency presents a real challenge in achieving a clean and sustainable environment. This study aims to analyze regional strategies for managing household waste based on Sumbawa Regent Regulation No. 46 of 2019 and to identify inhibiting factors in its implementation. The research employs a qualitative descriptive method through interviews, observations, and documentation. The findings reveal that waste management strategies in Sumbawa adopt the waste management hierarchy principles reduce, reuse, recycle, recovery, and disposal. However, their implementation still faces challenges such as limited funding, low community awareness, and ineffective inter-agency coordination. This study highlights the importance of cross-sector collaboration and community involvement in building sustainable environmental resilience.